Neurophysiology of male sexual arousal—Behavioral perspective - Bogacki-Rychlik, Wiktor; Gawęda, Katarzyna; Bialy, Michal (Frontiers in Behavioral Neuroscience, 2024)
In the presented review, we analyzed the physiology of male sexual arousal and its relation to the motivational aspects of this behavior. We highlighted the distinction between these processes based on observable physiological and behavioral parameters. Thus, we proposed the experimentally applicable differentiation between sexual arousal (SA) and sexual motivation (SM). We propose to define sexual arousal as an overall autonomic nervous system response leading to penile erection, triggered selectively by specific sexual cues. These autonomic processes include both spinal and supraspinal neuronal networks, activated by sensory pathways including information from sexual partner and sexual context, as well as external and internal genital organs. To avoid misinterpretation of experimental data, we also propose to precise the term "sexual motivation" as all actions performed by the individual that increase the probability of sexual interactions or increase the probability of exposition to sexual context cues.Neuronal structures such as the amygdala, bed nucleus of stria terminalis, hypothalamus, nucleus raphe, periaqueductal gray, and nucleus paragigantocellularis play crucial roles in controlling the level of arousal and regulating peripheral responses via specific autonomic effectors.On the highest level of CNS, the activity of cortical structures involved in the regulation of the autonomic nervous system, such as the insula and anterior cingulate cortex, can visualize an elevated level of SA in both animal and human brains.From a preclinical perspective, we underlie the usefulness of the noncontact erection test (NCE) procedure in understanding factors influencing sexual arousal, including studies of sexual preference in animal models.Taken together results obtained by different methods, we wanted to focus attention on neurophysiological aspects that are distinctly related to sexual arousal and can be used as an objective parameter, leading to higher translational transparency between basic, preclinical, and clinical studies.